1994
DOI: 10.1128/iai.62.11.4825-4830.1994
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bacterial motility with human antiflagellar monoclonal antibodies attenuates Pseudomonas aeruginosa-induced pneumonia in the immunocompetent rat

Abstract: Two human monoclonal antibodies, directed against the type a and type b flagellar proteins of Pseudomonas aeruginosa, inhibited bacterial motility in vitro specifically and in a concentration-dependent manner. In order to determine if this decreased bacterial motility was associated with a decreased pathogenicity, the ability of these human antiflagellar monoclonal antibodies to attenuate P. aeruginosa-induced pneumonia in the rat was assessed. Incubation of P. aeruginosa with a 1:1 mixture of the human antifl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…d Apparent M r Ϫ adjusted molecular weight. (24,30). With at least one mouse MAb, i.e., that raised against the flagella of 170018, there was an association between M r and cross-reactivity (30).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…d Apparent M r Ϫ adjusted molecular weight. (24,30). With at least one mouse MAb, i.e., that raised against the flagella of 170018, there was an association between M r and cross-reactivity (30).…”
Section: Discussionmentioning
confidence: 98%
“…The membrane was removed and washed according to standard procedures. Primary antibody, either human anti-a flagellin MAb or human anti-b flagellin MAb (24), was added at a 1:1,000 dilution in Tris-buffered saline (TBS)-Tween and incubated overnight at 4°C with shaking. Washes were performed as outlined above with TBS-Tween.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have demonstrated the protective effects of antiflagellar antiserum or MAbs against lethal P. aeruginosa infections in a burn wound model (15,19,21,28,33,39) and in a pneumonia model (22,29). Landsperger et al (22) demonstrated that decreased bacterial motility by antiflagellar antibody is associated with a decreased pathogenicity of P. aeruginosa in rat model of pneumonia (22). As a mechanism of protective effects of antiflagellar antibodies, Anderson and Montie (3,4) reported that antiflagellar antibodies stimulate opsonophagocytosis of P. aeruginosa by polymorphonuclear leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, strategies evaluating either different monovalent antigens from serogroup O2 strains in humans or monoclonal antibodies to this epitope may identify broadly reactive and protective antibodies with potential as immunotherapeutic agents. Alternative antigenic targets to LPS O antigens have been intensely investigated, with outer membrane proteins (OMPs) (8,11,16,40) and flagella (21) receiving the most attention. However, levels of antibodies to O antigens are clearly correlated with resistance to lethal outcomes during human infection (38).…”
Section: Discussionmentioning
confidence: 99%